Factors related with adherence score to iron chelation treatment in thalassemia patient (study at RSUD Tidar Magelang in 2019) - Adiratna, Widia (BKM Public Health and Community Medicine, 2021)
Objective: This study is to analyze the factors associated with adherence score to iron chelation treatment in thalassemia patients at RSUD Tidar Magelang in 2019. Methods: Quantitative methods are used in this research.An analytical study was carried out with a cross-sectional design with total sampling. Subjects were thalassemia patients who had routine transfusions at RSUD Tidar in 2019.A list of patients was obtained from the transfusion visit book at Thalassemia’s Room, RSUD Tidar. Primary data was collected by interview using a standardized questionnaire. Interview with parents is done for respondents below 16 years old. The statistical test used was Pearson correlation and Independent sample t-test. Results: Of the 90 patients on the list, 84 were successfully interviewed. From that, 54 (64,4%) patients had an adherence score of iron chelation medication below the average. Duration of taking medication from patients was 1-16 years with an average of 7.5 years Results of bivariate analysis show that age (p=0,086;r=-0,189),sex (p=0,737;r=0,190),knowledge about thalassemia (p=0,000;r=0,491-0,554),knowledge about iron chelation (p=0,000;r=0,554), family support (p=0,000;r=0,570), health workers support (p=0,000; r=0,468), duration of taking medicine(p=0,040;r=-0,224),side effects (p=0,000;r=-0,518),access to hospital (p=0,403) and type of iron chelation (p=0,023). Conclusions: It can be concluded that knowledge about thalassemia, knowledge about iron chelation, family support, health workers support, side effects of medicine, type of iron chelation, duration of taking medicine have a significant relationship with adherence score to taking iron chelation in thalassemia patient. Update on knowledge related to thalassemia and iron chelation is needed for patients and their families. Attention and motivation from families and health workers are needed, especially for patients who are bored with treatment.